Sociodemographic characteristics of patients, applied to substance usage disorders unit of gaziantep university - Bulut, Mahmut; Savaş, Haluk A.; Cansel, Neslihan; Selek, Salih; Kap, Özlem; Yumru, Mehmet; Vırıt, Osman (Journal of Dependence, 2006)
Objective: The aim of the study was to investigate the sociodemographic characteristics of patients who were applied to the Substance Usage Disorders Unit of Gaziantep University in past five years. Method: We evaluated retrospectively, the medical records of the patients who were applied to the Substance Usage Disorders Unit of Gaziantep University Medical Faculty Hospital in the last five years. All the data were collected and analyzed by SPSS for Windows 10.0. Results: The sample of the study consisted of 126 patients with alcohol and substance dependence and were examined in the past five years. The average age of the sample was 36.02 (SD±11.37) and beginning age to substance use was 13.19 (SD ±10.87) years. Most of the patients were male (96.8%) and 3.2% of the patients were female. Alcohol (46.8%), heroin (42.1%) and kannabis (7.1%) were the most frequently type of used substances. The mean age of first alcohol use of alcocohol dependants were 24.03 (SS±8.53) years and the mean age of first substance use of substance dependants were 22.44 (SS±7.15) years. Rate of marriage were significantly higher in alcohol dependent patients than drug dependent patients (p<0.001). The mean age of alcohol users were significantly higher than drug users (p<0.001). Unemployment rate was higher in drug users than alcohol users (p=0.009). Crime rates were significantly higher in the drug user (p=0.001). Crime rates were significantly higher in the patients who have lower educational level (p<0.001). Conclusion: This is the first study exploring sociodemographic characteristics of alcohol and substance dependent patients applied to a specific Substance Usage Disorders Unit in Gaziantep. The characteristics of substance use is similar to the other areas of Turkiye. However the rate of female patients were fewer than other areas of Turkiye and the mean age of first substance use were higher than other areas of Turkiye. This result may due to sociocultural characteristics of this area.